Green banking policy and implementation in Islamic banking: Evidence from Bank Syariah Indonesia Surabaya through a Maqāṣid al-Sharīʿah perspective - Mulyani, Khalishah; Susanti, Neneng Desi; Nurhayati , Nurhayati (Journal of Islamic Economics Lariba, 2026)
IntroductionGreen banking has become increasingly important in response to environmental degradation, climate risk, and the growing demand for sustainable finance. In Islamic banking, this issue is particularly significant because environmental responsibility can be interpreted not only as a managerial obligation but also as part of Maqāṣid al-Sharīʿah, especially the protection of life, wealth, and future generations. Despite the rapid growth of sustainability discourse, empirical studies that examine green banking implementation in Islamic banking at the branch level remain limited.ObjectivesThis study analyzes the policy and implementation of green banking at Bank Syariah Indonesia, Surabaya Branch, and evaluates its practices through the perspective of Maqāṣid al-Sharīʿah. It also seeks to identify the extent to which green banking has been institutionalized in financing, operations, and risk management.MethodThis study employed a qualitative approach with a field research design. Data were collected through in-depth interviews, observation, and documentation. The analysis focused on three main dimensions of green banking: green financing, green operations, and environmental and social risk management. The findings were then interpreted using the framework of Maqāṣid al-Sharīʿah.ResultsThe study finds that green banking at Bank Syariah Indonesia, Surabaya Branch has been implemented through sustainable financing practices, digital and paper-reducing operational measures, and the incorporation of environmental and social risk assessment into financing decisions. However, implementation remains partial. Sustainable financing still coexists with financing directed to environmentally harmful sectors, and internal environmental performance indicators such as energy, fuel, water, and paper use show fluctuation rather than consistent reduction. From the perspective of Maqāṣid al-Sharīʿah, these practices contribute to the protection of life, wealth, and intergenerational welfare, although their institutional integration remains incomplete.ImplicationsThe findings show that green banking in Islamic banking should be understood as an evolving institutional process rather than a completed transformation. The study highlights the need for stronger environmental literacy, more consistent operational integration, and more effective regulatory and governance support.Originality/NoveltyThis study contributes to the literature by offering a branch-level analysis of green banking in Islamic banking and by using Maqāṣid al-Sharīʿah as the primary evaluative framework rather than treating it as a symbolic ethical reference.